Organocatalytic Allylic Amination of Morita–Baylis–Hillman Carbonates - Formánek, Bedřich; Šimek, Michal; Kamlar, Martin; Císařová, Ivana; Veselý, Jan (Synthesis, 2019)
An organocatalytic asymmetric allylic amination of Morita–Baylis–Hillman carbonates with aromatic amines in the presence of β-isocupreidine is described. Chiral allylic amines were obtained in almost quantitative yields (90–96%) with moderate enantioselectivity. Recrystallization afforded products in good yields (45–73%) and high optical purity (82–99% ee). This method provides a facile and efficient route to obtain optically active β-lactams, including the building block of the cholesterol-lowering drug Ezetimibe.
Keywords: alkaloids; allylic amination; asymmetric synthesis; Ezetimibe; Morita–Baylis–Hillman carbonates; organocatalysis